CA10 regulates neurexin heparan sulfate addition via a direct binding in the secretory pathway. (15th February 2021) - Montoliu‐Gaya, Laia; Tietze, Daniel; Kaminski, Debora; Mirgorodskaya, Ekaterina; Tietze, Alesia A; Sterky, Fredrik H
Abstract: Neurexins are presynaptic adhesion molecules that shape the molecular composition of synapses. Diversification of neurexins in numerous isoforms is believed to confer synapse‐specific properties by engaging with distinct ligands. For example, a subset of neurexin molecules carry a heparan sulfate (HS) glycosaminoglycan that controls ligand binding, but how this post‐translational modification is controlled is not known. Here, we observe that CA10, a ligand to neurexin in the secretory pathway, regulates neurexin‐HS formation. CA10 is exclusively found on non‐HS neurexin and CA10 expressed in neurons is sufficient to suppress HS addition and attenuate ligand binding and synapse formation induced by ligands known to recruit HS. This effect is mediated by a direct interaction in the secretory pathway that blocks the primary step of HS biosynthesis: xylosylation of the serine residue. NMR reveals that CA10 engages residues on either side of the serine that can be HS‐modified, suggesting that CA10 sterically blocks xylosyltransferase access in Golgi. These results suggest a mechanism for the regulation of HS on neurexins and exemplify a new mechanism to regulate site‐specific glycosylations. Synopsis: CA10 binds to neurexins in the secretory pathway and blocks the addition of heparan sulfate to neurexins, which affects their ligand‐binding properties. These findings illustrate a new mechanism to regulate site‐specific glycosylations and a means to further diversify neurexin isoforms. Binding of the secreted protein CA10 to neurexins in the secretory pathway blocks the addition of heparan sulfate (HS) to neurexins. A direct interaction between CA10 and neurexin residues near the glycosylated serine prevents the primary step of HS biosynthesis: xylosylation of the serine residue. Abstract : CA10 binds the presynaptic adhesion molecules neurexin in the secretory pathway and inhibits their modification with heparan sulfate, thereby modifying the ligand‐binding properties of neurexin.